2006
DOI: 10.1128/aem.72.5.3111-3118.2006
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Gene Transfer of P IB -Type ATPases among Bacteria Isolated from Radionuclide- and Metal-Contaminated Subsurface Soils

Abstract: Aerobic heterotrophs were isolated from subsurface soil samples obtained from the U.S. Department of Energy's (DOE) Field Research Center (FRC) located at Oak Ridge, Tenn. The FRC represents a unique, extreme environment consisting of highly acidic soils with cooccurring heavy metals, radionuclides, and high nitrate concentrations. Four hundred isolates obtained from contaminated soil were assayed for heavy metal resistance, and a smaller subset was assayed for tolerance to uranium. The vast majority of the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 61 publications
5
89
1
1
Order By: Relevance
“…Decades of disposal of waste derived from uranium processing has led to acidic subsurface conditions that favor bacteria from the genus Rhodanobacter. Additionally, these conditions may have resulted in a dramatic die-off of other native soil bacteria, leading to conditions favoring lateral gene transfer (27,38). In the subsurface sediment from Area 3, the shallowest depth has a level of bacterial SSU rRNA gene sequence diversity consistent with that found in pristine soils (45; data not shown).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Decades of disposal of waste derived from uranium processing has led to acidic subsurface conditions that favor bacteria from the genus Rhodanobacter. Additionally, these conditions may have resulted in a dramatic die-off of other native soil bacteria, leading to conditions favoring lateral gene transfer (27,38). In the subsurface sediment from Area 3, the shallowest depth has a level of bacterial SSU rRNA gene sequence diversity consistent with that found in pristine soils (45; data not shown).…”
Section: Discussionsupporting
confidence: 58%
“…These periods of anoxia in the nitrate-rich subsurface, however, favor bacteria capable of denitrification. Martinez et al (38) suggested that metal sensitivity of native bacteria in the ORIFRC site subsurface likely facilitated the lateral gene transfer of metal resistance genes. Similarly, Rhodanobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon might be explained that microbial communities in the long-term field contaminated soil have already adapted to the toxic environment; therefore, microbial communities were more resistant to subsequent stress [38,39]. The adaption process of microorganisms to heavy metals might be emphasized by genetic or physiological changes of microorganisms (mutations or horizontal gene transfer) [40,41]. Moreover, at a community level, metal-sensitive species were substituted by metal-tolerant or metal-adapted species [42,43].…”
Section: Responses Of Soil Microorganisms To a Subsequent Stressmentioning
confidence: 99%
“…Subsequent studies indicated that the strain precipitated 95% of soluble uranium [U(VI)] as an insoluble autunite mineral during oxic and anoxic growth conditions when supplied with glycerol-3-phosphate as the sole carbon and phosphorus source (1, 2, 12). Additionally, recent microbial ecology studies of metal-, metalloid-, organic-, and radionuclide-contaminated soils have identified enrichments of Rahnella species that show promise for remediation strategies (6,10,13,15). Whole-genome sequencing was thus conducted on Rahnella sp.…”
mentioning
confidence: 99%
“…strain Y9602 is a gammaproteobacterium isolated from a mixed-waste-contaminated subsurface (i.e., low pH and high concentrations of nitrate, heavy metals, and radionuclides) at the U.S. Department of Energy (DOE) Oak Ridge Reservation in Oak Ridge, TN (13). Phenotypic characterization of Y9602 indicated resistance to heavy metals, uranium tolerance, and constitutive phosphatase activity.…”
mentioning
confidence: 99%